The pseudo viscous frictional energy dissipator a new device for mitigating seismic effects. - Wu, Bin (Earthquake engineering & structural dynamics.)
Viscous energy dissipators (EDORs) have good suppressing effects on acceleration or base shear and they do not add axial pressure to the column when peak moment in the column occurs at peak displacement. Pall frictional EDORs can dissipate energy even when the compression brace buckles due to a special frictional damping mechanism. Retaining the advantages of viscous and Pall EDORs and overcoming their disadvantages, a pseudo viscous frictional energy dissipator (PVEDOR) is developed. PVEDORs use the frictional damping mechanism of Pall EDORs, but the slip force of PVEDORs is made variable so that the slip force reduces with increasing displacement. Behaviour testing of PVEDORs shows that they possess the important hysteretic feature of viscous EDORs, i.e. the restoring force of PVEDORs are out of phase with displacement. Earthquake simulation tests of a 16 storey frame structure incorporating PVEDORs and ordinary steel braces and bare frame are carried out. The test results show that PVEDORs have good vibration suppressing effects. An analytical hysteretic model of PVEDORs basically agrees with the behaviour testing results. Finally, the parameter influence of PVEDORs on suppressive effectiveness of structural vibration under earthquake conditions is studied. Numerical analyses show that PVEDORs have good control effects on both seismic displacement and acceleration, and that control effects of PVEDORs on base shear are much better than Coulomb type frictional EDORs or metallic EDORs.